Separate visual pathways for perception of actions and objects: evidence from a case of apperceptive agnosia. Issue 3 (1st September 1998) - Ferreira, Carla Teixeira; Ceccaldi, Mathieu; Giusiano, Bernard; Poncet, Michel
Abstract : Recognition of different kinds of visual stimuli was studied in a patient who acquired apperceptive visual agnosia after a bilateral occipitotemporal lesion which partially spared the primary visual cortex. Impairment in recognising static objects perceived visually sharply contrasts with the relatively well preserved ability to recognise objects from gestures illustrating their use, and to recognise actions shown in line drawings. It is suggested that the occipitoparieto-frontal pathway is involved in the recognition of actions, and in the recognition of objects when sensorimotor experience is evoked.